Anion effect on lithium electrodeposition from N‐propyl‐N‐methylpyrrolidinium bis(fluorosulfonyl)imide ionic liquid electrolytes. (10th October 2016) - Basile, Andrew; Bhatt, Anand I.; O'Mullane, Anthony P.
Graphical abstract: Electrodeposition of Li from N -propyl- N -methylpyrrolidinium bis(fluorosulfonyl)imide with LiFSI, LiTFSI, LiBF4, LiPF6 or LiAsF6 salts onto Pt and Li electrodes was undertaken to identify the most appropriate salt for Li metal battery applications. Abstract: The electrodeposition of lithium metal from room temperature ionic liquid (RTIL) electrolytes consisting of N -propyl- N -methylpyrrolidinium bis(fluorosulfonyl)imide (Pyr13 [FSI]) with LiFSI, LiTFSI, LiBF4, LiPF6 or LiAsF6 salts onto Pt and Li electrodes was undertaken to identify mechanistic details. Cyclic voltammetry at both Pt and Li electrodes is complicated by the chemical reaction between fresh/electrodeposited Li metal and electrolyte to form a solid-electrolyte interphase (SEI). As such, all electrolyte systems depict quasi-reversible cycling, owing to the concomitant chemical breakdown of the electrolyte and deposition of a passivation product onto the electrode surface. The rate at which the SEI forms can be observed through cyclic voltammetric scan rate studies. Chronoamperometry data supports the cyclic voltammetry studies and indicates that an instantaneous nucleation and growth type mechanism is taking place at all potentials as determined through modelling the current-time transients utilising the Hills-Scharifker theory. We show herein that these RTIL based electrolytes can be cycled effectively in an order of stability of salt inclusion as follows: LiBF4  > LiFSI > LiAsF6  > LiTFSI > LiPF6 .